Neglected Shoulder Presentation with Hand Prolapse: A Rare and Fatal Obstetric Complication Managed in a Rural Hospital - Shrestha, Uma; Aryal, B. (Journal of Karnali Academy of Health Sciences, 2018)
In the era of modern obstetric care, the neglected shoulder presentation is usually limited in developing countries which increase the risk of the morbidity and mortality of both mother and fetus. In the past, the reports about obstetric management of this serious complication were very few. In this case report, we aim to describe the neglected shoulder presentation at term pregnancy that caused fetal death and discuss management options for this rare obstetric complication during labor.